Keterkaitan Jumlah Daerah Termutasi pada Gen β-globin dengan Indeks Korpuskular Pembawa Sifat β-thalassemia - Priyambodo, Priyambodo; Nur Handayani, Niken Satuti (Jurnal Penelitian Sains, 2016)
Thalassemia is a genetic dissorder caused by point mutation on the globin gene that decreasing the corpuscular index on thalassemian, included the carrier of thalassemia. Three to five percents of Indonesian is thalassemia carrier, β- thalassemia is the most common type. This research aimed to identify the relationship between the number of mutated region on β-globin gene and the decreasing of corpuscular index on β-thalassemia carrier. The data was collected during 2012 to 2014 in Yogyakarta. Hematological analysis was performed by corpuscular index included mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), and mean corpuscular haemoglobin concentration (MCHC) in Prodia Laboratory. Molecular analysis was performed by the polymerase chain reaction-single stand conformation polymorphism (PCR-SSCP) method in Laboratory of Genetics and Laboratory of Falitma, Biology Faculty, University of Gadjah Mada. Of a total of 96 individual screeaned, there were 9 suspects β-thalassemia carrier with 1 β-globin gene mutated region showed the average of MCV 63,1 fl, MCH 19,76 pg and MCHC 32,34 g/dl. Seven suspects β-thalassemia carrier with 2 β-globin gene mutated regions showed the average of MCV 61,16 fl, MCH 19,74 pg, and MCHC 32,3 g/gl. One suspect β-thalassemia carrier with 3 β-globin gene mutated regions showed the average of MCV 64,2 fl, MCH 19,5 pg, and MCHC 30,4 g/dl. The number of β-globin gene mutated region was not the main factor of decreasing the corpuscular index on β-thalassemia carrier.